The politics of welfare and governance in India: [Rezension von: Bussell, Jennifer, 1975-, Clients and Constituents - Jensenius, Francesca R., 1983-, Social justice through inclusion - Kruks-Wisner, Gabrielle, 1977-, Claiming the state - Singh, Prerna, 1979-, How solidarity works for welfare] - Jha, Himanshu (The journal of Asian studies, 2022)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911821002825/resource/name/firstPage-S0021911821002825a.jpg
Gesehen am 01.09.2022
Keywords: Rezension